In vitro and in vivo synergistic effects of tigecycline combined with aminoglycosides on carbapenem-resistant Klebsiella pneumoniae. (16th April 2021) - Ni, Wentao; Yang, Deqing; Guan, Jie; Xi, Wen; Zhou, Dexun; Zhao, Lili; Cui, Junchang; Xu, Yu; Gao, Zhancheng; Liu, Youning
Abstract: Objectives: Carbapenem-resistant Klebsiella pneumoniae (CR-KP) infections represent severe threats to public health worldwide. The aim of this study was to assess potential synergistic interaction between tigecycline and aminoglycosides via in vitro and in vivo studies. Methods: Antibiotic resistance profiles and molecular characteristics of 168 CR-KP clinical isolates were investigated by susceptibility testing, PCR and MLST. Chequerboard tests and time–kill assays were performed for 20 CR-KP isolates to evaluate in vitro synergistic effects of tigecycline combined with aminoglycosides. A tissue-cage infection model of rats was established to evaluate in vivo synergistic effects. Different doses of tigecycline and aminoglycosides alone or in combination were administered for 7 days via tail vein injection. Antibiotic efficacy was evaluated in tissue-cage fluid and emergence of resistance was screened. Results: The chequerboard tests showed that this combination displayed synergistic or partial synergistic activity against CR-KP. The time–kill assays further demonstrated that strong synergistic effects of such a combination existed against isolates that were susceptible to both drugs but for resistant isolates no synergy was observed if clinical pharmacokinetics were taken into consideration. The in vivo study showed that the therapeutic effectiveness of combination therapies was better than that of monotherapy for susceptible isolates, suggesting in vivo synergistic effects. Furthermore, combinations of tigecycline with an aminoglycoside showed significant activity in reducing the occurrence of tigecycline-resistant mutants. Conclusions: Compared with single drugs, tigecycline combined with aminoglycosides could exert synergistic effects and reduce the emergence of tigecycline resistance. Such a combination might be an effective alternative when treating CR-KP infections in clinical practice.